Examining Associations between Maternal Trauma, Child Attachment Security, and Child Behaviours in Refugee Families - Barnes, Jennifer; Theule, Jennifer (Refuge: Canada's Journal on Refugees, 2023)
We examined post-traumatic stress disorder (PTSD) and depressive symptoms in refugee mothers and the relationships between maternal trauma, child attachment security, and child internalizing and externalizing behaviours. Results from 36 mothers of children 18–70 months old indicated that while 94.4% of mothers reported experiencing trauma, only 2.8% reported clinically elevated PTSD symptoms. Maternal PTSD symptoms were correlated with child internalizing and externalizing behaviours. Attachment security was negatively correlated with internalizing and externalizing behaviours. Attachment security moderated the relationship between PTSD symptoms and externalizing behaviours; PTSD symptoms predicted externalizing behaviours for children with low attachment security only. This suggests that child attachment security may protect against maternal trauma.